2018
DOI: 10.1007/s00381-018-3870-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical histopathology of limited dorsal myeloschisis with flat skin lesion

Abstract: Immunopositivity for GFAP in the LDM stalk was observed in as few as 50% of our patients, despite the relatively extensive histopathological examination. We confirm that the clinical diagnosis of LDM should be made based on comprehensive histopathological examination as well as clinical manifestations. The profuse network of peripheral nerve fibers in every stalk and the high incidence of melanocyte accumulation associated with dermal melanocytosis might assist the histopathological diagnosis of LDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…In our patient, the typical histopathological finding of an LDM stalk was noted at the most rostral side of the intradural stalk. The presence of peripheral nerve fibers in the fibrocollagenous stalk and arachnoid tissue in the meningocele sac strongly supports the diagnosis of LDM [4, 5]. Another notable histopathological finding is that almost the entire stalk, except for the stalk-sac attachment, contained stratified squamous epithelium.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our patient, the typical histopathological finding of an LDM stalk was noted at the most rostral side of the intradural stalk. The presence of peripheral nerve fibers in the fibrocollagenous stalk and arachnoid tissue in the meningocele sac strongly supports the diagnosis of LDM [4, 5]. Another notable histopathological finding is that almost the entire stalk, except for the stalk-sac attachment, contained stratified squamous epithelium.…”
Section: Discussionmentioning
confidence: 77%
“…The central histopathological feature of an LDM stalk is GFAP-immunopositive neuroglial tissue in the fibrocollagenous band, which is a hallmark of the stalk’s origin from the incompletely disjoined neuroectoderm [1-5, 17]. In our patient, the typical histopathological finding of an LDM stalk was noted at the most rostral side of the intradural stalk.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…When conservative follow-up is selected, postoperative MRI including 3D-hT2WI is needed for the detection of newly developed dermoid cysts. Although the 2- to 5-mm-thick sections provided by conventional MRI are unable to demonstrate sufficiently detailed imaging, 3D-hT2WI can provide high-resolution images with excellent contrast between solid structures and the CSF [6, 7, 16-18]. The present study revealed that 3D-hT2WI with a slice thickness of 0.50–1.25 mm clearly demonstrated the spherical enlargement of the stalk, which is the characteristic finding of development of a dermoid cyst, on the contrast with CSF [18].…”
Section: Discussionmentioning
confidence: 99%
“…Saccular LDM is characterized by a skin-based cerebrospinal fluid (CSF) sac topped by a squamous epithelial dome. Flat LDM is characterized by squamous epithelium (SE) with a flat surface or sunken crater or pit, typically called “cigarette-burn” skin lesion [6, 7].…”
Section: Introductionmentioning
confidence: 99%